2010
DOI: 10.1371/journal.pone.0013573
|View full text |Cite
|
Sign up to set email alerts
|

Early Embryonic Gene Expression Profiling of Zebrafish Prion Protein (Prp2) Morphants

Abstract: BackgroundThe Prion protein (PRNP/Prp) plays a crucial role in transmissible spongiform encephalopathies (TSEs) like Creutzfeldt-Jakob disease (CJD), scrapie and mad cow disease. Notwithstanding the importance in human and animal disease, fundamental aspects of PRNP/Prp function and transmission remains unaccounted for.Methodology/Principal FindingsThe zebrafish (Danio rerio) genome contains three Prp encoding genes assigned prp1, prp2 and prp3. Currently, the second paralogue is believed to be the most simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Our attempts to establish prp2 MO reagents met with some success, reproducing aspects of previous studies [27], [28]. However, these reagents failed to meet the most stringent tests of reagent specificity [29], insofar as we could not rescue the prp2 knockdown phenotypes with prp2 mRNA, consistent with previous reports [27].…”
Section: Resultssupporting
confidence: 84%
“…Our attempts to establish prp2 MO reagents met with some success, reproducing aspects of previous studies [27], [28]. However, these reagents failed to meet the most stringent tests of reagent specificity [29], insofar as we could not rescue the prp2 knockdown phenotypes with prp2 mRNA, consistent with previous reports [27].…”
Section: Resultssupporting
confidence: 84%
“…We also observed evidence of NMD or loss of protein in selected mutants supporting the fact that many are likely null alleles, yet we still observed a high false-positive morphant phenotype rate. Consistent with these observations, recent studies have reported inconsistencies between morphants and mutants for individual genes, including phenotypes affecting lymphatic development (nr2f2, Aranguren et al, 2011; Swift et al, 2014; van Impel et al, 2014), neuronal function ( mfn2 and prp2 , Chapman et al, 2013; Fleisch et al, 2013; Nourizadeh-Lillabadi et al, 2010; Vettori et al, 2011), hindbrain patterning ( gbx2 , Kikuta et al, 2003; Su et al, 2014), and lateral line development ( tcf7 , Aman et al, 2011). Taken together with our broader findings here, these studies raise a major concern about relying solely on the application of MOs for primary characterization of gene function in the zebrafish.…”
Section: Discussionmentioning
confidence: 78%
“…30 In zebrafish, onset of endogenous PrP expression occurs within one day post fertilization (dpf). 2,29 From recent RNAseq (RNA deep sequencing) derived early zebrafish development transcriptomes, it can be registered that PrP-2 is present as maternal RNA and persists until early gastrula (50% gastrula epiboly at 5.3 hours post fertilization hpf), while PrP-1 is not present during this very early stage of development. 31 Morpholino knock-down experiments have demonstrated that the fish prion genes are essential for embryo survival, which is contrary to findings in knockout mice.…”
Section: Prion Protein Functions and Early Embryonic Development In Zmentioning
confidence: 99%
“…Thus, further studies are needed on both the molecular pathology and biological function of PrP. The nomenclature for prion protein variants and the corresponding genes can be confusing 2 and in this paper we have chosen standard mammalian prion gene and protein nomenclature for mammals (PRNP to denote the gene and PrP to denote the protein). For simplicity we here use PrP and PrP to denote the zebrafish genes and proteins, respectively.…”
mentioning
confidence: 99%